The Fiscal Crisis of the United Kingdom - McLean, I. author. aut Link
XXI, 250 p. 5 illus., 1 illus. in color.
Keywords: The system for allocating public expenditure to the nations and regions of the UK has broken down. Money goes to Scotland, Wales and Northern Ireland by the notorious Barnett formula, but this is collapsing and cannot last long. Money goes to the English regions by poorly-understood formulae that work badly. People in every region think that the system is unfair to them. The Fiscal Crisis of the United Kingdom suggests how the system could be fixed, drawing lessons from Australia and Canada. It recommends a Territorial Grants Commission.